KEANEKARAGAMAN DAN PENYEBARAN Selaginella spp. DI INDONESIA DARI TAHUN 1998-2014 - Wijayanto, Andik (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2014)
Selaginella is a single genus of ferns allies belong to Selaginelaceae family that lives in moist areas and it is often found in highlands which spread approximately 700 species all over the world. Some Selaginella species have wide distribution and tend to be invasive, but the others are endemics or endangered. The diversity study and distribution of Selaginella in Indonesia fom 1998 until 2014 was done by exploring Selaginella articles from many source. In Indonesia from 1998 until 2014, there were found about 39 species of Selaginella, namely S. alligans, S. alutacia, S. angustiramea, S. apoensis, S. aristata, S. biformis, S. caudata, S. ciliaris, S. cupressina, S. delicatula, S. doederleinii, S. frondosa, S. illanosii, S. intermedia, S. involvens, S. ketra-ayam, S. kraussiana, S. longiaristata, S. magnifica, S. mayeri, S. modica, S. nummularia, S. opaca, S. ornata, S. padangensis, S. plana, S. remotifolia, S. repanda, S. rothertii, S. rupestris, S. singalanensis, S. spinulosa, S. subalpina, S. uncinata, S. velutina, S. vonroemeri, S. wallichii, S. willdenovii, and S. zollingeriana that spread in the islands of Sumatera, Bangka-Belitung, Java, Bali, Kalimantan, Sulawesi, Lombok, Maluku, and Irian Jaya with different altitude and patterns of spread